In Vitro and In Vivo Response to Low-Modulus PMMA-Based Bone Cement - Carlsson, Elin (Biomed Res Int, 2015)
The high stiffness of acrylic bone cements has been hypothesized to contribute to the increased number of fractures encountered after vertebroplasty, which has led to the development of low-modulus cements. However, there is no data available on the in vivo biocompatibility of any low-modulus cement. In this study, the in vitro cytotoxicity and in vivo biocompatibility of two types of low-modulus acrylic cements, one modified with castor oil and one with linoleic acid, were evaluated using human osteoblast-like cells and a rodent model, respectively. While the in vitro cytotoxicity appeared somewhat affected by the castor oil and linoleic acid additions, no difference could be found in the in vivo response to these cements in comparison to the base, commercially available cement, in terms of histology and flow cytometry analysis of the presence of immune cells. Furthermore, the in vivo radiopacity of the cements appeared unaltered. While these results are promising, the mechanical behavior of these cements in vivo remains to be investigated.